Literature in Language Syllabus: Space and Contributions - Regmi , Lok Raj (Literary Studies, 2022)
This study explores the place of literature in language syllabus and analyzes how literature supports language enrichment, extensive reading and critical reading. Literature for language enrichment describes how literature supports the development of language skills in students. Literature for extensive reading deals with how literature supports the development of inferential and literary skills. Likewise, literature for critical reading describes how literature contributes to the development of intellectual skills in students. For this, theoretical and empirical studies have been consulted. Similarly, five teachers teaching English language/literature at university level as primary sources have been interviewed to collect data. The data collected from interviews have been discussed under four different themes. The study concludes that literature occupies an important space in language syllabus as literature is pedagogically, linguistically and aesthetically embedded. Literature in language syllabus is relevant to teach language skills, for example, listening, speaking, reading and writing. The study shows that literature provides the ground to teach literary and inferential skills: commenting, appreciating, characterizing, finding clues, developing supporting details, drawing conclusion. In addition, literature supports to teach intellectual skills: analyzing, synthesizing and interpreting using literary criticism.